2008
DOI: 10.1186/1471-2199-9-75
|View full text |Cite
|
Sign up to set email alerts
|

Normalisation genes for expression analyses in the brown alga model Ectocarpus siliculosus

Abstract: BackgroundBrown algae are plant multi-cellular organisms occupying most of the world coasts and are essential actors in the constitution of ecological niches at the shoreline. Ectocarpus siliculosus is an emerging model for brown algal research. Its genome has been sequenced, and several tools are being developed to perform analyses at different levels of cell organization, including transcriptomic expression analyses. Several topics, including physiological responses to osmotic stress and to exposure to conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 35 publications
5
116
1
3
Order By: Relevance
“…In addition to DNase-I treatment, remnants of genomic DNA contaminant were quantified by amplification of an intron and subtracted from the other values. EsEF1a was chosen as a constitutively expressed gene based on the study by Le Bail et al (2008b) and used for transcript-level normalization. The normalized data were expressed as means 6 SD calculated from the three independent biological experiments.…”
Section: Transcript-level Quantification By Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to DNase-I treatment, remnants of genomic DNA contaminant were quantified by amplification of an intron and subtracted from the other values. EsEF1a was chosen as a constitutively expressed gene based on the study by Le Bail et al (2008b) and used for transcript-level normalization. The normalized data were expressed as means 6 SD calculated from the three independent biological experiments.…”
Section: Transcript-level Quantification By Real-time Pcrmentioning
confidence: 99%
“…The levels of transcripts of EsGRP1 were quantified by real-time reverse transcription-PCR on three independent biological replicates. Each transcript level was normalized to EsEF1a transcripts, as recommended by Le Bail et al (2008b), and averaged (SD indicated). Asterisks indicate P , 0.05 with a t test.…”
Section: Role Of Auxin In E Siliculosus Developmentmentioning
confidence: 99%
“…The specificity, efficiency and dynamic range of the primers were tested on 1/5 serial dilutions of cDNA (range, 0.24-150 ng for elongation factor 1α [EF1a], vanadium-dependent bromoperoxidase [vBPO], manganese superoxide dismutase [MnSOD] and heat shock protein 70 [HSP70]; 0.12-75 ng for glutaredoxin [GRX]; 0.048-30 ng for glutathione S-transferase [GST]). The absence of genomic DNA contamination was examined in each sample with the intron-specific primer mN (Table 1) (Le Bail et al 2008).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…It has some significant advantages as an experimental model and constitutes one of the beststudied seaweeds (Peters et al 2004, Charrier et al 2008; it can easily be cultivated in small volumes of seawater media both axenically and with associated bacteria (Mül-ler et al 2008); it belongs to a sister group of the ecologically and economically very important kelps; its entire, well-known life cycle can be completed within a few months in culture; many molecular tools are available, including mutant collections (Peters et al 2004), microarrays (Dittami et al 2009) and proteomics . It has also recently become the first seaweed of which the entire genome has been sequenced and thus offers unprecedented opportunities for study (Cock et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation